Mathematical Study of Biting Rates of Mosquitoes in Transmission of Dengue Disease - Phaijoo, G. R.; Gurung, D. B. (Kathmandu University Journal of Science, Engineering and Technology, 2015)
The paper utilizes the SIR model to analyze the spread of the dengue disease, considering various biting rates of mosquitoes. Within the model, the human population is categorized into susceptible, infected, and recovered compartments, while the mosquito population is divided into susceptible and infected compartments. Through the calculation of the basic reproduction number, the study evaluates the transmission dynamics of dengue. Additionally, a sensitivity analysis is conducted to assess the significance of different model parameters in influencing disease transmission.